Stability Analysis of Isolated Hybrid Microgrid for Village Electrification - Singh, Kuldip; M. Narendra Kumar, Dr; Satyasis Mishra, Dr (International Journal of Engineering and Technology, 2018)
The village electrification is the main concern for government of India. The isolated Hybrid Microgrid with renewable energy sources has been growing rapidly for village electrification and it is going to play vital role for 100% electrification in rural area by 2020. For planning and designing of isolated hybrid microgrid the power system stability is major parameter and its main concern due to instability in load demand as well as in generation from renewable energy sources.Â  For renewable energy sources, the controlling of frequency and voltage deviation is a great challenge. This paper is carry out the stability analysis for PV-Biomass based isolated hybrid microgrid on different load and generation conditions and carry out the effect on frequency stabilityÂ